Laser Speckle Contrast Analysis: Functional Evaluation of Microvascular Damage in Connective Tissue Diseases. Is There Evidence of Correlations With Organ Involvement, Such as Pulmonary Damage? - Ruaro, Barbara; Bruni, Cosimo; Wade, Barbara; Baratella, Elisa; Confalonieri, Paola; Antonaglia, Caterina; Geri, Pietro; Biolo, Marco; Confalonieri, Marco; Salton, Francesco (Frontiers in Physiology, 2021)
Laser speckle contrast analysis (LASCA) is a noncontact technique able to quantify peripheral blood perfusion (PBP) over large skin areas. LASCA has been used to study hand PBP in several clinical conditions. These include systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) and LASCA showed that PBP was significantly lower in these conditions than in healthy subjects (HS). Moreover, it has been demonstrated that LASCA is a safe technique also able to monitor digital ulcer perfusion and their evolution in SSc patients, during systemic and local treatment. The use of LASCA, coupled with reactivity tests is commonplace in the ﬁeld of microvascular function research. Post-occlusive hyperemia reactivity (POHR) and local thermal hyperaemia, associated with laser techniques are reliable tests in the evaluation of perfusion in SSc patients. Other studies used laser speckled techniques, together with acetylcholine and sodium nitroprusside iontophoresis, as speciﬁc tests of endothelium function. In conclusion, LASCA is a safe, noncontact reliable instrument for the quantification of PBP at skin level and can also be associated with reactivity tests to monitor disease progression and re¬sponse to treatment in different connective tissue diseases.